An adhesive microneedle patch that quickly forms a film on the skin surface, and its preparation method and application

Through the microneedle patch matrix composition of polyvinylpyrrolidone and sodium hyaluronate, the problem of microneedle patch falling off in highly mobile parts is solved, rapid film formation and continuous adhesion of the skin surface is achieved, and the preparation process is simplified. Mass production.

CN118615232BActive Publication Date: 2025-01-03SHANDONG UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410652880.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-24
Publication Date
2025-01-03
Estimated Expiration
2044-05-24

AI Technical Summary

Technical Problem

Existing microneedle patches are prone to fall off when used in body parts with high mobility and large range of motion, resulting in interruption of drug delivery and difficult to achieve mass production.

Method used

Using a microneedle patch matrix composition of polyvinylpyrrolidone and sodium hyaluronate, a microneedle patch that can quickly absorb subcutaneous tissue fluid and hydrate is prepared to form a thin film by mixing it with ultrapure water and dissolving it in vacuum treatment and drying. to enhance adhesion.

Benefits of technology

The microneedle patch is quickly hydrated, dissolved and formed a thin film again in a short period of time, ensuring continuous adhesion on the surface of active skin such as joints, avoiding interruption of drug delivery, and simplifying the preparation process, suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118615232B_ABST
    Figure CN118615232B_ABST
Patent Text Reader

Abstract

The present invention discloses an adhesive microneedle patch with rapid film formation on the skin surface, and a preparation method and application thereof, which belongs to the technical field of microneedle patches. The matrix components of the adhesive microneedle patch include polyvinyl pyrrolidone and two or more sodium hyaluronates with different molecular weights. The matrix components are dissolved in water and blended to prepare a microneedle patch with skin adhesion, which can quickly absorb subcutaneous tissue fluid after acting on the skin, so that the microneedle body and the substrate are rapidly hydrated and dissolved in a short time, and the dissolved substrate forms a thin film on the skin surface again and adheres to the skin surface. The patch is suitable for use on active skin surfaces such as finger joints, elbow joints, knee joints and ankle joints, and will not cause drug delivery interruption problems caused by patch shedding and detachment from the skin.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microneedle patches, and in particular to an adhesive microneedle patch capable of forming a quick film on the skin surface, and a preparation method and application thereof. Background Art

[0002] Drug-loaded microneedle technology provides a new platform for safe, controllable and efficient transdermal drug delivery, and is widely used in the fields of blood sugar management, vaccination and skin disease treatment. However, most microneedles themselves do not have adhesion and are only suitable for use on flat skin surfaces. When applied to body parts with high mobility and large range of motion (such as joints), microneedle patches can easily fall off the skin, resulting in interrupted drug delivery. Therefore, the development of skin-adhesive microneedle patches suitable for long-term and sustainable delivery of drugs to highly active body parts (joints, hands and legs, etc.) is of practical significance for broadening the scope of application of drug-loaded microneedles.

[0003] Inspired by the adhesion mechanism of mussels and octopus tentacles in nature, the research group of Professor Zhao Yuanjin of Nanjing University (Research.2020May;2020:UNSP 3672120.) introduced the suction cup microstructure of octopus tentacles into the microneedle substrate, and used polydopamine gel as the substrate material to develop a multifunctional flexible microneedle with skin adhesion. It can adhere firmly to the skin in both dry and wet environments, and shows excellent adhesion when applied to joints. In addition, shark tooth-like drug-loaded microneedles (ACS Nano. 2021 Sep; 15 (9): 15316-15327.), porcupine quill-like barbed drug-loaded microneedles (Acta Biomaterialia. 2023 April; 160: 32-44.), and blue-ringed octopus sucker-like drug-loaded microneedles (Science Advances. 2023 June; 9 (25): 2213.) all exhibit excellent adhesion properties on skin and tissues, and can achieve sustained and long-term delivery of loaded drugs into the body. However, the above-mentioned microneedle preparation methods all rely on specially made microneedle molds, and the microneedle preparation process is relatively cumbersome and is not suitable for mass production of adhesive drug-loaded microneedles. Summary of the invention

[0004] The purpose of the present invention is to provide an adhesive microneedle patch that quickly forms a film on the skin surface, and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art. The adhesive dissolving microneedle patch that quickly forms a film on the skin surface provided by the present invention can quickly absorb subcutaneous tissue fluid after acting on the skin, so that the microneedle body and the substrate are rapidly hydrated and dissolved in a short time, and the dissolved substrate forms a thin film on the skin surface again and adheres to the skin surface.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The present invention provides a microneedle patch matrix composition, comprising polyvinyl pyrrolidone and two or more sodium hyaluronates of different molecular weights;

[0007] The molecular weight of the polyvinyl pyrrolidone is 8-40 kDa, and the molecular weight of the sodium hyaluronate is 3-500 kDa.

[0008] Furthermore, the mass ratio of the polyvinyl pyrrolidone to the sodium hyaluronate is (5-25):(14-35).

[0009] The present invention also provides application of the microneedle patch matrix composition in improving the adhesion of the microneedle patch to the skin.

[0010] The present invention also provides the use of the microneedle patch matrix composition in preparing an adhesive microneedle patch that quickly forms a film on the skin surface.

[0011] The present invention also provides an adhesive microneedle patch that quickly forms a film on the skin surface. The matrix component of the adhesive microneedle patch includes the microneedle patch matrix composition.

[0012] Further, the matrix of the adhesive microneedle patch includes the microneedle patch matrix composition;

[0013] The preparation method of the matrix comprises mixing and dissolving the microneedle patch matrix composition with ultrapure water to prepare a matrix solution, and then subjecting the solution to vacuum treatment and drying to obtain a matrix solution; in the matrix solution, the mass fraction of polyvinyl pyrrolidone is 2-40%, and the mass fraction of sodium hyaluronate is 1-40%.

[0014] Furthermore, the matrix component of the adhesive microneedle patch also includes small molecule additives.

[0015] Furthermore, the small molecule additive includes one or more of trehalose, sucrose, tripropylene glycol methyl ether, magnesium chloride, calcium hydrogen phosphate and sodium bicarbonate.

[0016] Furthermore, the adhesive microneedle patch also includes an active ingredient.

[0017] Furthermore, the active ingredients include one or more of chemical drugs and biological drugs.

[0018] The present invention discloses the following technical effects:

[0019] The microneedle patch matrix composition provided by the present invention is prepared into a microneedle patch with skin adhesion after being dissolved and blended in water. The microneedle patch can quickly absorb subcutaneous tissue fluid after acting on the skin, so that the microneedle body and the substrate are quickly hydrated and dissolved in a short time. The dissolved substrate forms a thin film on the skin surface again and adheres to the skin surface. The patch is suitable for use on active skin surfaces such as finger joints, elbow joints, knee joints and ankle joints, and will not cause the problem of drug delivery interruption caused by patch shedding and detachment from the skin.

[0020] The microneedle patch matrix composition provided by the present invention can also be prepared into a microneedle matrix together with other small molecule additives, and further loaded with active ingredients to prepare a drug-loaded microneedle patch, which has the advantages of safe and environmentally friendly preparation materials, simple and fast preparation process, and easy mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 Schematic diagram of the use process of the adhesive microneedle patch that quickly forms a film on the skin surface;

[0023] Figure 2 The figure shows the flexibility of the microneedles made in experimental groups 1-3;

[0024] Figure 3 The skin adhesion test diagram of the microneedles prepared in the experimental group 4 and the comparative groups 4-7;

[0025] Figure 4 The skin adhesion test image of the drug-loaded microneedles prepared in experimental group 5-6;

[0026] Figure 5 This is a test diagram of the adhesion performance of the microneedle patch prepared in experimental group 7-8 at the skin joint;

[0027] Figure 6 The mechanical strength test curve of the microneedles prepared in experimental groups 4-6;

[0028] Figure 7 The morphology of the microneedles prepared in experimental groups 4-6 after mechanical strength testing;

[0029] Figure 8 This is a test chart of the irritation of the microneedles made in experimental group 4-5 to rat skin within 24 hours;

[0030] Fig. 9This is the in vitro transdermal release curve of the microneedles prepared in experimental groups 5-6. DETAILED DESCRIPTION

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0032] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0036] Unless otherwise specified, the raw materials used in the embodiments of the present invention can be obtained from commercial sources.

[0037] In the embodiments of the present invention, polyvinyl pyrrolidone is referred to as PVP, sodium hyaluronate is referred to as HA, polyvinyl alcohol is referred to as PVA, and carboxymethyl cellulose is referred to as CMC.

[0038] The present invention provides an adhesive dissolving microneedle patch that can form a film on the skin surface quickly. Its matrix composition includes polyvinyl pyrrolidone and sodium hyaluronate, which are polymer materials that are fast-soluble in water and can form a film. Among them, polyvinyl pyrrolidone includes two or more specifications with different molecular weights. After the microneedle patch penetrates the skin, the matrix material absorbs the tissue fluid in the skin and quickly dissolves and hydrates, and adheres to the local skin. After the backing layer is peeled off, the hydrated matrix contacts the air and quickly forms a film, and adheres to the skin surface, making it suitable for use on active skin surfaces such as finger joints, elbow joints, knee joints or ankle joints. It does not cause the problem of drug delivery interruption caused by the patch falling off and detaching from the skin, and realizes the continuous drug delivery application on the skin surface of the joints and bends (such as Figure 1 shown).

[0039] Example 1 Preparation of flexible microneedles suitable for use on joints and bends

[0040] According to the microneedle base solution formula in Table 1, a 10 mL centrifuge tube was used as a container, and the corresponding volume of ultrapure water and the corresponding mass of matrix material were measured and added to the centrifuge tube in turn. A stirring rod was used to stir to promote the complete dissolution of the solution, and the microneedle matrix solutions of different formulas were obtained after centrifugation to remove bubbles. The microneedle solutions of each prescription were added to the polydimethylsiloxane (PDMS) mold unit at a volume of 20 μL / well. After negative pressure vacuum treatment, the solution was filled into the needle tip unit and continued to dry at room temperature overnight to obtain microneedle preparations of different formulas.

[0041] Table 1 Microneedle base liquid composition formula of experimental group 1-3 and comparison group 1-3

[0042]

[0043] The dried microneedles of the above different formulations were peeled off from the mold and folded in half using tweezers to examine the flexibility of the microneedle preparations of each formulation. The results are shown in Tables 1 and Figure 2 As shown. The microneedles made from the experimental groups 1-3 formulas can be demolded smoothly after molding, and the microneedles in each group show good flexibility ( Figure 2 ), however, the microneedles made from the formulations of the comparison groups 1-3 could not be demolded smoothly after molding and broke into pieces when lightly touched (Table 1), indicating that the microneedles of the comparison groups 1-3 did not have flexibility and were not suitable for skin attachment.

[0044] Example 2 Skin Adhesion Test of Rapid Film-forming and Dissolving Microneedles on Skin Surface

[0045] According to the microneedle base liquid formula in Table 2, microneedles with different base liquid formulas were prepared according to the preparation method of Example 1.

[0046] Table 2 Microneedle base liquid composition formula of experimental group 4 and comparison groups 4-7

[0047]

[0048]

[0049] The microneedles prepared according to the base solution formula of experimental group 4 and comparison groups 4-7 were subjected to in vitro skin and in vivo skin adhesion tests. The details are as follows:

[0050] (1) In vitro pig skin adhesion test:

[0051] The back skin of one-month-old suckling pigs was depilated and subcutaneous fat was removed to obtain ex vivo pig skin with a thickness of about 800 μm. The skin was cut into 2 cm × 2 cm pieces and spread on a self-adhesive transparent plate with the stratum corneum facing upward. The microneedle basal layer was fixed to a homemade needle inserter, and the microneedle was applied to the stratum corneum side of the skin through the needle inserter. After pressing hard for 10 seconds, the external force was removed, and the needle inserter was removed vertically upward to observe and record the adhesion between the microneedle and the ex vivo pig skin.

[0052] (2) In vivo rat abdominal skin adhesion test:

[0053] 24 hours before the test, the abdominal hair of SD rats was removed using clippers and depilatory cream to obtain a 2cm×2cm dosing area. 24 hours later, the microneedle patches of each prescription were applied to the skin of the depilatory area through a needle inserter. After pressing for 20 seconds, the needle inserter was removed, and the microneedle patch was allowed to remain on the local skin for 30 minutes before the hydrogel backing was removed. The adhesion between the microneedle and the abdominal skin of the living rats was observed and recorded.

[0054] (3) Human knuckle skin adhesion test:

[0055] The microneedle patches of each prescription were applied to the skin surface of the finger joints of volunteers using a hydrogel backing. After pressing for 20 seconds, the microneedle patches were allowed to remain on the local skin for another 30 minutes before the hydrogel backing was peeled off. The adhesion between the microneedles and the skin of the human finger joints was observed and recorded.

[0056] The skin adhesion test results of the microneedles prepared according to different base liquid formulas in Table 2 are as follows Figure 3 shown.

[0057] The results of the in vitro pig skin adhesion test showed that the microneedles prepared with the formula of experimental group 4 produced strong adhesion after acting on the ex vivo pig skin, which was manifested as the skin and the transparent plate underneath were lifted up as a whole after the needle inserter with the microneedles fixed on it was removed from the skin surface, indicating that after a brief contact, the microneedles and the skin surface generated adhesion force; in contrast, the microneedles prepared with the formulas of comparison groups 4-7 were completely separated from the skin after the needle inserter was removed, indicating that the four types of microneedles in the above comparison groups did not have the ability to adhere to the skin.

[0058] The results of the mouse skin adhesion test showed that the microneedles prepared with the formula of experimental group 4 quickly dissolved and hydrated after acting on the abdominal skin of living rats, and after removing the hydrogel backing, the hydrated matrix material formed a film again and adhered tightly to the skin surface, promoting the formation of adhesion between the drug-loaded microneedle patch and the skin; in contrast, after the needle inserter was removed, the microneedles prepared with the formula of comparison groups 4-7 had a smooth skin surface with no matrix material attached or residual, and only a clear array of pinholes, indicating that there was no adhesion between the microneedles and the rat skin.

[0059] The results of the human skin adhesion test showed that the microneedles prepared by the formula of experimental group 4 quickly dissolved and hydrated after acting on the human knuckle skin, and after removing the hydrogel backing, the hydrated matrix material formed a film again and adhered tightly to the skin surface. During the retention period of the microneedles and after removing the hydrogel backing, the knuckles could move freely without causing problems such as the microneedle patch lifting and detaching from the skin, thereby ensuring the continuous and long-term drug delivery of the drug-loaded microneedles in the local skin. In contrast, after the hydrogel backing was removed, the microneedles prepared by the formulas of comparison groups 4-7 could easily detach from the skin surface with the backing because the adhesion force between the hydrogel backing and the microneedle basal layer was much greater than the interaction force between the microneedle patch and the skin. This was manifested as no matrix material residue and adhesion on the knuckle skin surface after the action, and only a clear array of pinholes was distributed, indicating that the microneedle patches prepared by the formulas of comparison groups 4-7 did not have skin adhesion properties.

[0060] The above shows that only when the microneedle base liquid selects two or more PVPs with different molecular weights and then combines them with HA in a specific ratio can the microneedle patch have a certain flexibility and adhesion.

[0061] Example 3 Skin Adhesion Test after Microneedle Drug Loading

[0062] According to the microneedle base solution and active ingredient formulas in Table 3, microneedles with different base solution formulas were prepared according to the preparation method of Example 1.

[0063] Table 3 Microneedle formulations of experimental groups 5 and 6

[0064]

[0065] The microneedles prepared according to the formulas of experimental groups 5 and 6 were subjected to in vitro and in vivo skin adhesion tests respectively according to the method of Example 3. The results are shown in FIG. Figure 4 The drug-loaded microneedle patches applied on ex vivo pig skin, living rat abdominal skin, and volunteer finger joint skin all showed similar in vivo and in vitro skin adhesion effects as those of experimental group 4, indicating that under the conditions of specific matrix materials and ratios, drug loading will not affect the adhesion of microneedles, making it have good application prospects in the field of drug delivery.

[0066] Example 4: Skin Adhesion Test of Microneedles Containing Small Molecule Additives

[0067] According to the microneedle base liquid formula in Table 4, microneedles with different base liquid formulas were prepared according to the preparation method of Example 1.

[0068] Table 4 Microneedle base solution formula of experimental groups 7-9

[0069]

[0070]

[0071] The microneedle patches of the experimental group 7-9 were applied to the skin surface of the volunteers' finger joints using a hydrogel backing. After pressing for 20 seconds, the microneedle patches were left on the local skin for another 60 minutes. During this period, the volunteers moved normally, with their fingers freely stretched and bent, and the adhesion between the microneedles and the skin of the finger joints was observed and recorded. The test results are as follows: Figure 5 As shown in the figure, after the microneedles are fixed to the finger joints through the hydrogel backing, they do not affect the normal extension and bending of the joints. After 1 hour of application, the hydrogel backing is removed and it is found that the microneedles of the three formulas are hydrated and quickly form films on the skin surface, tightly adhering to the skin surface, and will not fall off the skin as the hydrogel backing is torn off, indicating that the microneedle patch containing small molecule additives also has excellent skin adhesion ability.

[0072] Example 5 Skin adhesion test of microneedles after loading with different types of drugs

[0073] According to the microneedle base solution and active ingredient formulas in Table 5, microneedles with different base solution formulas were prepared according to the preparation method of Example 1.

[0074] Table 5 Formulas of the matrix and active ingredients of drug-loaded microneedles in experimental groups 10-15

[0075]

[0076] After the microneedles were prepared, the skin adhesion properties of the microneedles in each group were tested on the abdominal skin of SD rats, and the test results are shown in Table 5. This shows that the adhesive dissolving microneedles with rapid film formation on the skin surface prepared by PVP and HA with a specific molecular weight and compatibility ratio are suitable for loading different types of drugs, and do not affect the skin adhesion ability of the microneedle patch, and are suitable for long-term and continuous drug delivery in highly active parts of the body such as joints, hands and legs.

[0077] Example 6 Mechanical Strength Test of Skin Adhesive Microneedle Patch

[0078] The mechanical strength of the skin-adhesive microneedle patch was tested using a force-displacement tester. The microneedles prepared from the formulas of experimental groups 4-6 were fixed to the stage using double-sided tape (3M), with the needle tip facing up. The stage moved toward the probe (2mm×2mm) at a speed of 1.1mm / s. The number of microneedles tested each time was 16, and the axial force was set to 10N acting on the microneedle tip. After completion, the three sets of microneedle data were plotted using Origin software, and the tested microneedles were placed under an optical microscope to observe the fracture / bending of the needle tip, and the mechanical properties of the skin-adhesive microneedle patch at different drug loadings were compared.

[0079] The test results are as follows Figure 6 and Figure 7 As shown, the microneedle patches prepared by the formulas of experimental groups 4-6 all showed good mechanical strength, among which the blank microneedles of experimental group 4 had the best mechanical strength, which was manifested as the smallest displacement of the needle tip of the microneedles of this formula under the same force conditions, followed by the drug-loaded microneedles of experimental group 5, and the drug-loaded microneedles of experimental group 6 had relatively poor mechanical strength, but they could effectively pierce the skin stratum corneum barrier. The above results show that the drug loading is negatively correlated with the mechanical properties of the microneedles, and the increase in drug content leads to a decrease in the mechanical strength of the microneedles. After the test, the tips of the three groups of microneedles were bent without breaking, indicating that the composition of the microneedle matrix material has both excellent mechanical strength and flexibility.

[0080] Example 7 Skin safety test of skin adhesive microneedle patch

[0081] 24 hours before the test, the abdominal hair of SD rats was removed with clippers and depilatory cream to obtain a 4cm×4cm administration area. 24 hours later, the microneedles prepared with the formulas of experimental group 4 and experimental group 5 were applied to the skin of the depilatory area of ​​the rats, and the microneedle patches were removed after continuous application for 12 hours. The local skin reactions and skin irritation were observed and recorded to evaluate the skin safety performance of the microneedle patches.

[0082] The results are as follows Figure 8 As shown in the figure, after 12 hours of application of the microneedle patches prepared with the formulas of experimental groups 4 and 5, an adhesive film was formed on the skin at the microneedle application site, which was consistent with the results described above. At this time, the local skin had slight redness, which was due to the damage of the skin stratum corneum by the microneedle puncture, which was a normal phenomenon; after 6 hours, the pinholes on the skin surface healed, and there was no pinhole array distribution visible to the naked eye; after 12 hours, the skin erythema faded, and the skin color returned to the state before the microneedle was used; after 24 hours, new hair grew on the skin in the microneedle application area, indicating that the prepared skin-adhesive microneedle patch had good biocompatibility and skin safety.

[0083] Example 8 In vitro transdermal drug release test of skin adhesive microneedle patch

[0084] The modified Franz diffusion cell method was used to evaluate the in vitro transdermal drug release performance of the drug-loaded skin adhesive microneedle patch. The ex vivo porcine skin was cut into uniform thickness and size using a puncher and a scalpel, placed in PBS buffer at 37°C for pre-equilibration for 60 minutes, and then taken out. The moisture on the stratum corneum side was wiped dry with absorbent paper. The microneedle patches prepared with the formulas of experimental group 5 and experimental group 6 were placed on the stratum corneum of the skin, respectively, and pressed for 20 seconds using a needle inserter to ensure that the microneedles penetrated the skin. The treated skin was fixed on the transdermal cup, and a quantitative PBS receiving solution was injected into the receiving pool. The magnetic stirring speed of the diffusion pool was set to 300 rpm, and the water bath temperature was set to 37°C. At the preset time point, the receiving solution was collected and re-injected with fresh PBS buffer. After the receiving solution was filtered through a 0.22 μm microporous membrane, the drug content in the receiving solution was measured by high performance liquid chromatography, and the cumulative skin permeation of the drug was calculated.

[0085] The results are as follows Fig. 9 As shown, the 24h cumulative drug permeation of the two groups of microneedles were 220.51±11.13μg / mL and 476.11±27.55μg / mL, respectively. According to the drug loading amount (experimental group 5 - 250μg / piece, experimental group 6 - 500μg / piece), the 24h drug transdermal permeability of the two microneedles reached more than 75%, indicating that the drug-loaded skin adhesive microneedle patch can act on the skin surface to release drugs steadily for 24 hours.

[0086] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.32 g of sodium hyaluronate with a molecular weight of 10 kDa, 0.16 g of sodium hyaluronate with a molecular weight of 250 kDa and 3.520 mL of ultrapure water.

2. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.28 g of sodium hyaluronate with a molecular weight of 100 kDa, 0.2 g of sodium hyaluronate with a molecular weight of 240 kDa and 3.520 mL of ultrapure water.

3. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 40 kDa, 0.24 g of sodium hyaluronate with a molecular weight of 5 kDa, 0.24 g of sodium hyaluronate with a molecular weight of 300 kDa and 3.520 mL of ultrapure water.

4. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 10 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.12 g of sodium hyaluronate with a molecular weight of 250 kDa and 3.360 mL of ultrapure water.

5. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 10 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.12 g of sodium hyaluronate with a molecular weight of 200 kDa, 3.280 mL of ultrapure water and 0.08 g of matrine.

6. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 40 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 8 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.12 g of sodium hyaluronate with a molecular weight of 300 kDa, 3.208 mL of ultrapure water and 0.15 g of matrine.

7. A microneedle patch matrix composition, characterized in that: The ingredients are 0.16 g of polyvinyl pyrrolidone with a molecular weight of 8 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 5 kDa, 0.18 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.08 g of trehalose and 3.280 mL of ultrapure water.

8. A microneedle patch matrix composition, characterized in that: The ingredients are 0.24 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.28 g of sodium hyaluronate with a molecular weight of 8 kDa, 0.2 g of sodium hyaluronate with a molecular weight of 120 kDa, 0.12 g of tripropylene glycol methyl ether and 3.400 mL of ultrapure water.

9. A microneedle patch matrix composition, characterized in that: The ingredients are 0.12 g of polyvinyl pyrrolidone with a molecular weight of 40 kDa, 0.24 g of sodium hyaluronate with a molecular weight of 15 kDa, 0.24 g of sodium hyaluronate with a molecular weight of 480 kDa, 0.20 g of sodium bicarbonate and 3.440 mL of ultrapure water.

10. A microneedle patch matrix composition, characterized in that: The ingredients are 0.20 g of polyvinyl pyrrolidone with a molecular weight of 8 kDa, 0.36 g of sodium hyaluronate with a molecular weight of 5 kDa, 0.10 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.18 g of sucrose, 3.180 mL of ultrapure water and 0.12 g of paeoniflorin.

11. A microneedle patch matrix composition, characterized in that: The ingredients are 0.22 g of polyvinyl pyrrolidone with a molecular weight of 15 kDa, 0.30 g of sodium hyaluronate with a molecular weight of 10 kDa, 0.40 g of sodium hyaluronate with a molecular weight of 38 kDa, 3.260 mL of ultrapure water and 0.20 g of Bletilla striata polysaccharide.

12. A microneedle patch matrix composition, characterized in that: The ingredients are 0.12 g of polyvinyl pyrrolidone with a molecular weight of 15 kDa, 0.20 g of sodium hyaluronate with a molecular weight of 3 kDa, 0.20 g of sodium hyaluronate with a molecular weight of 500 kDa, 0.05 g of magnesium chloride, 3.660 mL of ultrapure water and 0.08 g of lidocaine.

13. A microneedle patch matrix composition, characterized in that: The ingredients are 0.50 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.16 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.20 g of sodium hyaluronate with a molecular weight of 200 kDa, 3.360 mL of ultrapure water and 0.10 g of exenatide.

14. A microneedle patch matrix composition, characterized in that: The ingredients are 0.10 g of polyvinyl pyrrolidone with a molecular weight of 10 kDa, 0.50 g of sodium hyaluronate with a molecular weight of 38 kDa, 0.10 g of sodium hyaluronate with a molecular weight of 480 kDa, 0.03 g of calcium hydrogen phosphate, 3.450 mL of ultrapure water and 0.08 g of bovine serum albumin.

15. A microneedle patch matrix composition, characterized in that: The ingredients are 0.32 g of polyvinyl pyrrolidone with a molecular weight of 8 kDa, 0.20 g of sodium hyaluronate with a molecular weight of 10 kDa, 0.08 g of sodium hyaluronate with a molecular weight of 500 kDa, 3.510 mL of ultrapure water and 0.05 g of diclofenac sodium.

16. Use of the microneedle patch matrix composition according to any one of claims 1 to 15 in improving the adhesion of a microneedle patch to the skin.

17. Use of the microneedle patch matrix composition according to any one of claims 1 to 15 in preparing an adhesive microneedle patch that rapidly forms a film on the skin surface.